Kerjasama Antara Guru Bimbingan Dan Konseling Dengan Guru Pendidikan Agama Islam Dalam Mengendalikan Emosi Belajar Siswa Di MAN 4 Kediri - Muhamad Faiz Amiruddin; Durrotul Lami'ah (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2022)
Emotions are the most important part in human life, because it is through these emotions that humans can express their feelings, while a person's ability to control and direct his emotions towards something will greatly affect his situation and environment. The research we use uses quantitative methods and survey methods because we can get data that happened in the past or present. With this technique, we can collect information from the group represented by the resource person. Guidance is help or guidance or it can also be interpreted as help. However, in this context not all assistance or assistance can be said to be a guidance within the scope of guidance and counseling. At MAN 4 Kediri the form of cooperation carried out by BK teachers and PAI teachers is to provide a direction to students in the academic field such as directing lecture majors for class 12. As well as building and developing good morals in students. In collaboration between BK teachers and PAI teachers can said to not face any obstacles due to direct and intense communication. Although there are not enough BK teachers available. However, the presence of PAI teachers or classroom teachers has been very helpful in solving all the problems experienced by students, not only that at MAN 4 Kediri BK teachers and PAI teachers also instill Islamic attitudes and good morals in each student.